2021
DOI: 10.3389/froh.2021.751099
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Smoking on Subgingival Plaque and the Development of Periodontitis: A Literature Review

Abstract: Smoking seriously affects oral health and causes a variety of oral diseases. Numerous clinical data show that smoking significantly increases the risk of periodontitis, and the duration and amount of smoking are positively correlated with the severity of periodontitis. In fact, smoking creates an environment conducive to the colonization of periodontopathogens, which affects the process of periodontitis. Since subgingival plaque which harbors periodontopathogens is the initiation factor of periodontitis, it is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 78 publications
1
11
0
1
Order By: Relevance
“…Smoking enhances the pathogenicity of periodontopathogens, especially the red complex microorganisms, by promoting their colonization and infection and regulating the expression and function of multiple virulence factors. Furthermore, smoking hurts periodontal microecological homeostasis, which is reflected in the decrease of commensal bacteria and the increase of periodontopathogens, as well as the changes in the interaction between periodontopathogens and their commensal microbes in subgingival biofilm, thus influencing the pathogenicity of the subgingival plaque [16].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking enhances the pathogenicity of periodontopathogens, especially the red complex microorganisms, by promoting their colonization and infection and regulating the expression and function of multiple virulence factors. Furthermore, smoking hurts periodontal microecological homeostasis, which is reflected in the decrease of commensal bacteria and the increase of periodontopathogens, as well as the changes in the interaction between periodontopathogens and their commensal microbes in subgingival biofilm, thus influencing the pathogenicity of the subgingival plaque [16].…”
Section: Discussionmentioning
confidence: 99%
“…Im Vergleich zu Nichtrauchern weisen Raucher ein 90 % höheres Risiko auf. Des Weiteren treten aggressive Verläufe der Parodontitis bei Rauchern häufiger auf als bei Nichtrauchern [ 12 ].…”
Section: Auswirkungen Des Rauchens Auf Den Gastrointestinaltraktunclassified
“…Periodontitis is a chronic inflammatory disease, studies have shown that inflammation is the driving force behind neutrophil-mediated tissue degradation and alveolar bone loss in P. gingivalis-induced periodontitis [ 18 ]. Smoking increases the susceptibility of patients to infection of periodontopathogens and accelerates the progression of periodontitis via accelerating the destruction of periodontal supporting tissues, which increases the severity of periodontitis [ 19 ]. Pro-inflammatory T cell–derived cytokines such as interferon (IFN)-Îł and TNF-α and IL-17 A exacerbate hypertensive responses mediating both endothelial dysfunction and cardiac injury [ 20 ].…”
Section: Introductionmentioning
confidence: 99%